Ancho de banda en superficies selectivas en frecuencia tipo cruz de dipolo - Rodríguez-Barrera, Mario Alberto; Carpes-Jr, Walter Pereira (Revista Científica, 2018)
This paper presents the implementation outcomes of the Equivalent Circuit Model (ECM) acting in conjunction with the Matrix Cascading Method (MCM) for bandwidth calculation in cross dipole Frequency Selective Surfaces (FSSs). Dielectric layers are used as a support of resonant elements in FSSs. Models of effective permittivity of the dielectric layers in FSSs allow to determine the effect of the material used as insulating support of the resonant elements, in relation to the resonant frequency and bandwidth, as a function of the thickness of the dielectric material. However, in this approach, the insulating support is considered as thin dielectric, and therefore, it is modeled as a lumped parameter. This consideration may lead to unsuitable results in calculating the bandwidth for thick dielectric supports. The novelty of the paper is the implementation of the Equivalent Circuit Model together with the Matrix Cascading Method to determine the frequency response of the cross dipole selective surface for any dielectric thickness and configuration. It is notable the low computational time as well as the acceptable accuracy obtained with the proposed approach, compared to Ansys-HFSS simulations.